O mundo coberto de penas: uma análise cronotópica de Vidas secas, de Graciliano Ramos - Lopes, Lucas Jose de Mello (2023)
This dissertation focuses on the novel Barren lives [1938], by Graciliano Ramos. The work takes place in the rural space of the Brazilian Northeast, with characters attached to an unfavorable climate and the power relations defined by land property. The focus of the research is on how the reality of the rural chronotope, based on the context of production, is structurally reduced and radiates into the composition of the work. It aims to analyze the construction of rural space-time in Barren lives and its implications on other elements of the narrative. Specifically, it aims to: a) recover the social-literary process that shaped the work; b) analyze the image of the human being that arises from the connection between characters, space, time and power relations; and c) verify the development of attributes of the novel genre in the work. To this end, bibliographical research and literary analysis were carried out based on Antonio Candido's integrative criticism, Bakhtin's theory of the novel — especially the concept of chronotope — and Northrop Frye's theory of modes. The exercise revealed that the elaboration of spacetime dialogues with the reality of the country at the time of writing: Graciliano Ramos, faced with a Brazil based on disbelief, conceives a circular chronotope that assumes pre-novelistic forms that contradict the freedom and the creative initiative typical of the modern novel. In this chronotope, called here the bolandeira chronotope and based on a principle of opposition, cyclical time and space marked by oppressive power relations imprison Fabiano and his family in an apparently inescapable emergency. These characters, however, are endowed with an awareness of themselves and the world that elevates them in the midst of this reified universe. Although they cannot significantly alter the negative world in which they circulate, they resist and do not allow themselves to be contaminated by the oppressor's modus operandi. Thus, Ramos establishes a literary form that, while feeding on the feeling of disenchantment and failure of his generation, also tensions it by seeking a path of humanization contrary to the civilizing barbarism of his time based on apparently primitive characters